Label-free highly sensitive probe detection with novel hierarchical SERS substrates fabricated by nanoindentation and chemical reaction methods - Zhang, Jingran; Jia, Tianqi; Yan, Yongda; Wang, Li; Miao, Peng; Han, Yimin; Zhang, Xinming; Shi, Guangfeng; Geng, Yanquan; Weng, Zhankun; Laipple, Daniel; Wang, Zuobin (Beilstein Journal of Nanotechnology, 2019)
Nanostructures have been widely employed in surface-enhanced Raman scattering (SERS) substrates. Recently, in order to obtain a higher enhancement factor at a lower detection limit, hierarchical structures, including nanostructures and nanoparticles, appear to be viable SERS substrate candidates. Here we describe a novel method integrating the nanoindentation process and chemical redox reaction to machine a hierarchical SERS substrate. The micro/nanostructures are first formed on a Cu(110) plane and then Ag nanoparticles are generated on the structured copper surface. The effect of the indentation process parameters and the corrosion time in the AgNO3 solution on the Raman intensities of the SERS substrate with hierarchical structures are experimentally studied. The intensity and distribution of the electric field of single and multiple Ag nanoparticles on the surface of a plane and with multiple micro/nanostructures are studied with COMSOL software. The feasibility of the hierarchical SERS substrate is verified using R6G molecules. Finally, the enhancement factor using malachite green molecules was found to reach 5.089 × 109, which demonstrates that the production method is a simple, reproducible and low-cost method for machining a highly sensitive, hierarchical SERS substrate.
Keywords: Ag nanoparticles; hierarchical substrates; malachite green molecules; nanoindentation; nanostructures; R6G; SERS